Disenchantment revisited: Formations of the 'secular' and 'religious' in the technological discourse of modernity. (March 2015) - Han, Sam
This article problematizes sociologist Max Weber's famed notion of 'disenchantment' in order to explore the ways in which 'technology' and 'religion' operate in the discourse of 'secular modernity'. It suggests that disenchantment is not simply epistemological, that is, synonymous with rationalization and intellectualization, but also ontological, and a description of the overhauling of what Bruno Latour calls the 'modernist settlement'. It proceeds in following manner: (1) it presents an 'interpretive genealogy' of technological rationality in discourses about modernity, demonstrating an internal conflict, especially in how 'religion', 'the secular, ' and 'technology' are conceptualized. It posits that the lack of consistency in the invocation of these terms is a symptom of a deeper unresolved ontological (or, onto-cosmological) tension. (2) After establishing this ontological aporia, the article proceeds to offer a rereading of Weber's original concept of disenchantment. (3) Finally, the author teases out some of the implications of reading disenchantment ontologically for the understanding of religion and technology.